Essential listening for IELTS - Min, Hu (Nxb. Tp. Hồ Chí Minh ; Công ty Nhân Trí Việt, 2010)
The Book consists of 26 units with 52 lessons. The units in each level are based on topics which frequently appear in the real test. There are 3 sections in every lesson: 1. Pre-listening; 2. While listening; 3. Post listening.